Perioperative Medicine 2022
DOI: 10.1016/b978-0-323-56724-4.00039-3
|View full text |Cite
|
Sign up to set email alerts
|

Acute Respiratory Failure

Abstract: Acute respiratory failure occurs when the lungs fail to oxygenate arterial blood adequately and it is one of the commonest postoperative complications. The preoperative identification of risk factors for postoperative acute respiratory failure allows identification of those patients who may benefit from preoperative optimization and increased postoperative vigilance. Multiple postoperative pulmonary complications are associated with acute hypoxemic respiratory failure and this chapter discusses atelectasis, pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…During times of distress, there is increased physiologic pulmonary arteriovenous shunting and hypoxemia [22]. In a study by Porter et al, obesity was observed to be an independent predictor of respiratory failure in severe acute pancreatitis [23]. A study by Lankisch et al further concluded that obesity increases the incidence of shock, renal insufficiency, and respiratory insufficiency, necessitating artificial ventilation [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…During times of distress, there is increased physiologic pulmonary arteriovenous shunting and hypoxemia [22]. In a study by Porter et al, obesity was observed to be an independent predictor of respiratory failure in severe acute pancreatitis [23]. A study by Lankisch et al further concluded that obesity increases the incidence of shock, renal insufficiency, and respiratory insufficiency, necessitating artificial ventilation [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Respiratory failure occurs due to a disease or injury worsening the lungs’ ability to deliver oxygen or remove carbon dioxide ( Summers et al , 2022 ). Symptoms of acute respiratory failure occur suddenly and can be life threatening ( Summers et al , 2022 ). It requires immediate medication or oxygen supplementation.…”
Section: Introductionmentioning
confidence: 99%
“…NIV is a breathing support technique that significantly improves gas exchange and vital signs, reducing intubation by 20% and mortality rates by 13% [ 3 ]. It is usually recommended for patients with COVID-19-related acute hypoxemic respiratory failure (AHRF) [ 4 ], which has the following main causes: hypoventilation, diffusion impairment, shunt, and ventilation-perfusion (V/Q) mismatch [ 5 ].…”
Section: Introductionmentioning
confidence: 99%